2018
DOI: 10.1161/circulationaha.117.031403
|View full text |Cite
|
Sign up to set email alerts
|

Association of Spontaneous Preterm Delivery and Future Maternal Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) risk factors are well established. However, little is known about a woman's cardiovascular response to pregnancy, which appears to be an early marker of future maternal CVD risk. Spontaneous preterm delivery (sPTD) has been associated with a ≤3-fold increased risk of maternal CVD death later in life compared with having a term delivery. This review focuses on 3 key areas to critically assess the association of sPTD and future maternal CVD risk: (1) CVD risk factors, (2) inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…PTB not only poses risk to the child, but it may also identify women with elevated lifetime risk for CVD (96). Indeed, women with PTB are more likely to have CV events and increased hospitalization rates (97) Robbins et al reported a significant increase in the incidence of AMI, stroke and CAD in these women (98). Compared with normal term delivery, spontaneous preterm delivery (sPTD) has been…”
Section: Preterm Birthmentioning
confidence: 99%
“…PTB not only poses risk to the child, but it may also identify women with elevated lifetime risk for CVD (96). Indeed, women with PTB are more likely to have CV events and increased hospitalization rates (97) Robbins et al reported a significant increase in the incidence of AMI, stroke and CAD in these women (98). Compared with normal term delivery, spontaneous preterm delivery (sPTD) has been…”
Section: Preterm Birthmentioning
confidence: 99%
“…All-cause PTDs are associated with a 1.5-to 3-fold higher risk of CVD [1][2][3][4]6]. Previous studies have shown that much of this association is accounted for by metabolic disorders during pregnancy, especially preeclampsia (which explains about 24-26% of the association) [1], or by metabolic disorders postpartum (which may explain about 13-15% of the association) [3]; however, a substantial portion of the risk remains unaccounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that much of this association is accounted for by metabolic disorders during pregnancy, especially preeclampsia (which explains about 24-26% of the association) [1], or by metabolic disorders postpartum (which may explain about 13-15% of the association) [3]; however, a substantial portion of the risk remains unaccounted for. The PTD-CVD associations persist even in pregnancies uncomplicated by preeclampsia or hypertensive disorders [3,6,7], indicating the need to explore other pathways via which PTD and CVD are linked. PTD is heterogeneous, with a variety of different PTD subtypes (i.e., spontaneous vs. medically indicated PTD), with and without preeclampsia, which may affect CVD risk through different pathways.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Several risk factors related to pregnancy have been identified as affecting younger women. In a review of associations between preterm delivery and future maternal cardiovascular disease, Minissian et al suggested that abnormal responses to pregnancy were a woman's first physiological “stress test.” 9 Veerbeek et al found that 39% of women with pregnancy-induced hypertension continued to have elevated blood pressure in the postpartum period. 10 Gestational diabetes has also been linked to an increased lifetime risk of type 2 diabetes (T2DM), a coronary heart disease equivalent.…”
Section: Introductionmentioning
confidence: 99%